A 5V, 20MHz Bandwidth, fully differential Operational Amplifier with 70 V/μs Slew Rate and 205 ns/30 ns enable/disable time in 180 nm CMOS - Mai, Timo; Weigel, Robert (IEEE International Symposium on Industrial Electronics, 2020)
When the enable-pin of an Opamp is used for modulation, or it is powered down due to power consumption considerations, the turn-on and turn-off time delay are critical [6]. Here we present a differential Opamp that works as differential amplifier. It uses adaptive biasing in common mode feedback circuit and power stages. It has a slewrate of 70 V/μs, an on-delay of 205 ns and an off-delay of 30 ns. To the best of our knowledge, the latter is the fastest ever published. It is fabricated in 180 nm CMOS with 1.04xl.26mm chip area and draws 9mA out of 5V.
CRIS-Team Scopus Importer:2020-08-28
Keywords: adaptive biasing; gain boosting; monticelli; operational amplifier; process variations